Talking Dialogue Eleven Episodes in the History of the Modern Interreligious Dialogue Movement - Lehmann, Karsten (KAICIID - Beyond Dialogue Series, 2021)
The modern dialogue movement has gained worldwide significance. Based upon genuine archival work, the authors of the present book reconstruct the history of the movement from 1900 to 2000. Looking at central episodes in the history of 11 international dialogue organizations, they identify 3 distinct groups that are shaping the movement: individual religious virtuosi, countercultural activists, and representatives of religious institutions.